The presence of diabetic retinopathy closely associated with the progression of non-alcoholic fatty liver disease: A meta-analysis of observational studies - Zhang, Guo-heng; Yuan, Tian-hao; Yue, Zhen-sheng; Wang, Lin; Dou, Guo-Rui (Frontiers in Molecular Biosciences, 2022)
Background and Objective: Although growing evidence indicates that non-alcoholic fatty liver disease is related to diabetic retinopathy (DR), research results significantly vary. Therefore, we conducted a meta-analysis to assess the association between the progression of non-alcoholic fatty liver disease and the onset of DR. Methods: PubMed, Embase, and Cochrane databases were searched until 7 November 2021. Combined odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the association. Results: We identified 18 studies involving 12,757 patients. The pooled effect assessment showed that liver fibrosis was positively correlated with DR (OR = 1.69, 95%CI 1.30–2.20; p < 0.0001); non-alcoholic fatty liver disease was not associated with the risk of DR (OR = 1.15, 95%CI 0.75-1.76; p = 0.51); non-alcoholic fatty liver disease was positively correlated with DR in patients with type 1 diabetes (OR = 2.96, 95%CI 1.48–5.94; p = 0.002). In patients with type 2 diabetes, there was no association between non-alcoholic fatty liver disease and DR (OR = 0.92, 95%CI 0.59–1.43; p = 0.70). Subgroup analysis showed no correlation in both Asian and Caucasian races. Conclusion: There is a significant correlation between liver fibrosis and DR. This suggests that the ocular examination of DR could be helpful in predicting whether patients with non-alcoholic fatty liver disease would progress to liver fibrosis.